Distinct class of putative “non-conserved” promoters in humans: Comparative studies of alternative promoters of human and mouse genes - Tsuritani, Katsuki; Irie, Takuma; Yamashita, Riu; Sakakibara, Yuta; Wakaguri, Hiroyuki; Kanai, Akinori; Mizushima-Sugano, Junko; Sugano, Sumio; Nakai, Kenta; Suzuki, Yutaka (Genome Research, 2007)
Although recent studies have revealed that the majority of human genes are subject to regulation of alternative promoters, the biological relevance of this phenomenon remains unclear. We have also demonstrated that roughly half of the human RefSeq genes examined contain putative alternative promoters (PAPs). Here we report large-scale comparative studies of PAPs between human and mouse counterpart genes. Detailed sequence comparison of the 17,245 putative promoter regions (PPRs) in 5463 PAP-containing human genes revealed that PPRs in only a minor fraction of genes (807 genes) showed clear evolutionary conservation as one or more pairs. Also, we found that there were substantial qualitative differences between conserved and non-conserved PPRs, with the latter class being AT-rich PPRs of relative minor usage, enriched in repetitive elements and sometimes producing transcripts that encode small or no proteins. Systematic luciferase assays of these PPRs revealed that both classes of PPRs did have promoter activity, but that their strength ranges were significantly different. Furthermore, we demonstrate that these characteristic features of the non-conserved PPRs are shared with the PPRs of previously discovered putative non-protein coding transcripts. Taken together, our data suggest that there are two distinct classes of promoters in humans, with the latter class of promoters emerging frequently during evolution.